Efforts to Equitable Education for Children with Intellectual Disabilities as an Alternative to Overcoming Social Problems in Children (Universitas Negeri Semarang, 2020)
Children with disabilities have the same rights in terms of getting an education, like normal children in general, children with disabilities also have high aspirations. To achieve these goals, of course, they must get equal and adequate educational facilities regardless of their shortcomings. In order to achieve equal distribution of education for children with disabilities, the government is expected to improve educational facilities and infrastructure for those with disabilities. Because even though children with disabilities have shortcomings, their abilities cannot be doubted. The reason is, there are many children with disabilities who have good intellectual achievements and abilities, therefore the need for government and community awareness to open their eyes more for children with disabilities so that they can be more confident in achieving their goals. Public awareness is also needed because children with disabilities also need to get support from the surrounding environment in order to avoid social problems for themselves caused by being isolated from society or the environment. Because this will have an impact on their own future. For people with intellectual disabilities, it will be very difficult to develop their potential if they do not get adequate and equal education. Education for persons with disabilities is implemented in the national education system through inclusive education and special education. Include children with disabilities in the 12 (twelve) year compulsory education program. In addition to having intellectual limitations, people with disabilities also have limitations in communication, social skills, self-care, health and safety, ability to do something (work), participation in a community, and academic limitations. This factor is the problem with the general public